2013
DOI: 10.4046/trd.2013.75.6.256
|View full text |Cite
|
Sign up to set email alerts
|

Successful Rechallenge with Imatinib in a Patient with Chronic Myeloid Leukemia Who Previously Experienced Imatinib Mesylate Induced Pneumonitis

Abstract: Imatinib mesylate is a targeted therapy that acts by inhibiting tyrosine kinase of the bcr-abl fusion oncoprotein, which is specific to chronic myeloid leukemia (CML), and the c-transmembrane receptor, which is specific to gastrointestinal stromal tumors. Interstitial pneumonitis is a rare adverse event of imatinib therapy. It is clinically difficult to distinguish from infectious pneumonia, which can frequently occur due to the underlying disease. The standard treatment for imatinib-induced pneumonitis is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Incidence appears to be higher in those with pre-existing lung disease [5]. In the present case, the development of pneumonitis occurred after five months of treatment.…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 57%
See 2 more Smart Citations
“…Incidence appears to be higher in those with pre-existing lung disease [5]. In the present case, the development of pneumonitis occurred after five months of treatment.…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 57%
“…Imatinib pneumonitis appears to develop on average approximately two months after commencing treatment with a median dose of 400mg imatinib [4,5]. Incidence appears to be higher in those with pre-existing lung disease [5].…”
Section: Cancer Therapy and Oncology International Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although not frequent, it was shown that IM can also induce pneumonitis in patients with CML [6][7][8]. In the study by Ohnishi et al [9], among 5500 patients receiving IM, there were 27 cases of interstitial lung disease.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Surgery is the preferred therapy if the metastases are resectable, and chemotherapy is an option when surgery is not feasible. The drugs used at relapse are usually gemcitabine and docetaxel [response rates (RR) 15-30%] [5][6][7], high-dose ifosfamide [RR 30-40%] [8,9] or etoposide.…”
mentioning
confidence: 99%